Business Plan and its Implementation on Bakery Business: A Case Study of Laziza Bakery - Muhammad Ahnaf Zalfa Rahmat (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This research evaluates Laziza Bakery's performance compared to its initial business plan, with a focus on operational efficiency, market positioning, and strategic adaptation in Kebumen, Central Java, during January-June 2024. The analysis covered various aspects of the business, including financial performance, workflows, customer engagement, and market response. The results highlighted notable revenue growth, with an index of 198, and a growth rate of 8% in June 2024. Key successes included product innovation, effective customer relationship management, and improved workflow processes. The bakery's digital transformation also proved successful, with online engagement exceeding expectations by 25%. Customer satisfaction remained high (above 4,5 out of 5), while operational efficiency increased by 15%. Laziza Bakery achieved growth by diversifying its product offerings by 30% and increasing revenue by 25%. In conclusion, the bakery has established a sustainable growth model, driven by a broad product range, efficient distribution, and a robust digital presence.